Soil Evolution and Mass Flux of Basaltic Cinder Cones in a Cool, Semi‐Arid Climate. Issue 5 (23rd August 2018) - Vaughan, Karen L.; McDaniel, Paul; Strawn, Daniel; Blecker, Steve
Abstract : Core Ideas: Soil development across a chronosequence of basaltic cinder cones. Elemental mass balance data were used to investigate secondary mineral formation. Elucidate rates and processes of early stage weathering. Soil developmental processes on young volcanic cinders in cool, semiarid climates are not well understood and previously under‐studied, but present a unique setting within which to study neoformation of soils under well‐dated time constraints. This study investigates the development of physical, chemical, and mineralogical soil properties on a chronosequence of basaltic cinder cones, aged approximately 2.1, 6.9, and 13.9 ka, at Craters of the Moon National Monument and Preserve in southern Idaho. Representative parent material, coarse fragments, and soil samples were analyzed using selective dissolutions and total elemental digests. Elemental mass balance data were used together with the soil physicochemical data to investigate weathering and secondary mineral formation within each soil profile. The highest degree of weathering was identified on the 13.9 ka profile, followed by the 6.9 and 2.1 ka soils. Short‐range ordered minerals, including allophane and ferrihydrite, dominate the colloidal fraction of all soils, with greatest proportions in the oldest soil. Dominant soil‐forming processes documented along the chronosequence of basalt‐derived soils are the accumulation of organic carbon, weathering of rock fragments, loss of base cations, redistribution of Fe, Al, and Ti, and the accumulation of secondary short‐range order and crystalline minerals. This study provides critical information to elucidate rates and processes of early stage weathering, dust influence, and soil evolution on cinders in cool and dry climates.